Los fuegos del Etna - Guzmán Arias, Carmen (Cuadernos de Filología Clásica. Estudios Latinos, 2003)
This work aims to analize the Latin texts that authors let us about the Aetna’s volcanic activity. Our research stars with some lucretian verses (VI 639-702), follows with other texts of the problematic poem Aetna and ends with two famous passages by Virgilio (Aen. III 570-587) and Ovid (Met. XV 340-355), all in order to know the literary treatment of a scientific matter.